EFFECTIVENESS OF USING PICTURE MEDIA ON LEARNING OUTCOMES OF GRADE II STUDENTS IN PKN LEARNING ON PANCASILA SYMBOL MATERIALS AT STATE ELEMENTARY SCHOOL 091254 BATU ONOM - Hilda Wati Tinambunan; Jon Roi Tua Purba; Yanti Arasi Sidabutar (RADJA PUBLIKA, 2025)
This study aims to determine the effectiveness of using picture media on learning outcomes of Class II students in Civics Education on Pancasila symbols at SD Negeri 091254 Batuonom in the 2025/2026 academic year. The research method used is experimental with a quantitative approach, specifically a pre-experimental design using the One Group Pretest-Posttest Design. The sample consists of all 25 students in Class II, selected through total sampling. Data collection was done through a multiple-choice test of 25 items, which had previously undergone data analysis techniques. The data analysis was conducted using N-Gain analysis. The results of the N-Gain analysis show that the average normalized score is 0.79, with a moderate interpretation. The N-Gain analysis results also show that the average pre-test score is 44.8, and the average post-test score is 89.4, with the lowest N-Gain score being 60 and the highest being 100. This results in a gain of 0.79, indicating a high category of effectiveness in using picture media, as (g) ≥ 0.70. II students in Civics Education on Pancasila symbols at SD Negeri 091254 Batuonom in the 2025/2026 academic year.